Characterizing trachoma elimination using serology - Kamau. E.; Ante-Testard. P.A.; Yeboah-Manu. D.; et al. (Nature Communications, 2025)
Trachoma is targeted for global elimination as a public health problem by 2030. Measurement of IgG antibodies in children is being considered for surveillance and programmatic decision-making. There are currently no pro grammatic guidelines based on serology, which represents a generalizable problem in seroepidemiology and disease elimination. Here, we collate Chla mydia trachomatis Pgp3 and CT694 IgG measurements from 48 serosurveys across Africa, Latin America, and the Pacific Islands (41,168 children ages 1–5 years) and propose a novel approach to estimate the probability that population C. trachomatis transmission is below or above levels requiring ongoing programmatic action. We determine that trachoma programs could halt control measures with >90% certainty when seroconversion rates (SCRs) are ≤2.2 per 100 person-years. Conversely, SCRs ≥4.5 per 100 person-years correspond with >90% certainty that further control interventions are needed. More extreme SCR thresholds correspond with higher levels of confidence of elimination (lower SCR) or ongoing action needed (higher SCR). This study demonstrates a robust approach for using trachoma serosurveys to guide elimination program decisions.
Research Article